Invariance Analysis, Explicit Solution and Numerical Exact solution of Time Fractional Partial Differential Equation - et. al., Hemant Gandhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research article, we have performed invariance analysis to time fraction partial differential equation (FPDE) by Lie symmetry reduction and converted the fractional order system into fractional ordinary differential equation (FODE) with the application of Erdyli-Kober (E-K) differ-integral operators in Riemann-Liouville (R-L) sense. Exact solutions are being established by power series technique and numerical solutions have been verified with application of the Fractional Reduced Differential Transforms and Homotop Analysis Methods.